Analisis Kultur Sekolah Dalam Menciptakan Lingkungan Belajar Yang Kondusif Pada 5 Lembaga PAUD Di Kabupaten Ngada - Yasinta sangi; Maria Theresia Avila Nia; Nova KLaudia Wula; Yohana Elma Sarina Ito Wea; Yasinta Advensia Wea; Maria Eleonora Lejo; Maneldis Romana Ngode; Paulina Mao; Aprilia W. Bhoko Fao; Agata Mau Tegu; Irsan Sauda; Aloysia Seke; Yustina Wona; Maria Melania Ito; Oktavianey Wunga; Ririnsia Anjelin Go'o; Maria Trisanti Watu (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2026)
This research aims to analyze school culture in creating a conducive learning environment in five PAUD institutions in Ngada Regency. The main focus of the research includes the implementation of the 3S culture (Smile, Greet, Salam), early learning conditioning (morning routine), cleanliness culture, and children's independence. Using descriptive qualitative methods through observations and interviews, this research found significant performance gaps; four institutions showed optimal levels of children's participation and independence (average 85%-95%), while one institution (TKK Wajo) was below standard(41%-60%). In-depth analysis shows that the success of school culture is greatly influenced by the consistency of the teacher's role as a facilitator within the Independent Curriculum framework, as well as the availability of accessible physical facilities. The research results confirm that the transformation of the teacher's role from an instructional model to a learning facilitator is the main key in stimulating children's independence. This article recommends standardizing operational procedures (SOP) for morning routines and strengthening teacher professionalism through training in facilitation techniques to ensure equal distribution of the quality of education services for early childhood across all institutions.